Impact of stacking sequence on the thermal and electrical properties of Poly (aryl ether ketone)/glassfiber/buckypaper composites - Gomes, João Victor P. N. [UNESP]; Costa, Michelle Leali [UNESP]; Thomazini, Daniel; de Paula Santos, Luis Felipe [UNESP]; Ribeiro, Bruno [UNESP]; Botelho, Edson C. [UNESP] (Wiley, 2024)
The current market's imperative demand necessitates the research and development of advanced polymer composites, especially those incorporating nanofillers. Carbon nanotubes, in particular, have attracted significant attention within research and development for their potential in creating multifunctional composites. This study aims to evaluate the impact of incorporating carbon nanotube buckypapers (BP) on the thermal and electrical properties of poly (aryl ether ketone) (PAEK)/glass fiber (GF) composites. The BP was prepared through vacuum filtration and integrated into PAEK/GF composites with varying stacking sequences, followed by hot compression processing. The degradation behavior of the laminates was investigated using thermogravimetric analysis (TGA). The viscoelastic properties, evaluated by dynamic mechanical analysis (DMA), suggested an increase in stiffness with the inclusion of BP in two of the analyzed stacking sequences. Thermal conductivity, measured via the pulse laser method, showed results comparable to the base laminate (0.153 W/m·K). Meanwhile, electrical conductivity, assessed using the four-point probe method in the in-plane direction, revealed semiconductor properties, achieving a mean value of 3.162 S/cm for one of the samples, indicating electrical anisotropy within the multifunctional composite material.
Keywords: composites; conducting polymers; microscopy; nanostructured polymers; thermal properties